Reframing the reintegration of trafficked children, centering the role of family and community - Mbakogu , Ifeyinwa (American Journal of Social Sciences and Humanities, 2025)
Reintegration programs and policies informing them in West Africa are framed within Western notions of childhood and child development, which fail to account for relationships within family and community contexts that influence a child’s movement away from home. The paper is informed by ongoing research with trafficked children from West Africa, residing in shelters, or who have returned home to their identified family members or guardians. It draws on interview data and personal narratives that highlight both the diversity and complexity of children’s experiences across trafficking, rescue, and reintegration phases. The study found that on returning home, survivors are confronted with the trauma of their trafficking experiences, familial blame, silencing, shame, exclusion, and pressure to endure exploitation for the benefit of family honor and survival. The paper calls for reintegration practices for survivors of trafficking to be context-dependent processes that interrogate family and community interactions rather than assuming that they are supportive of survivors and their recovery. It emphasizes that reintegration efforts should be survivor-informed, culturally grounded, and designed to accommodate the unique needs of each child. The findings support family-and-community-inclusive interventions that transcend reunification to prioritize survivor narratives, address histories of power imbalances, stigma and coercion, and the nature of family obligations.